2019
DOI: 10.1111/resp.13575
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high‐flow therapy compared with non‐invasive ventilation in COPD patients with chronic respiratory failure: A randomized controlled cross‐over trial

Abstract: Background and objective: Non-invasive ventilation (NIV) is part of the standard of care for hypercapnic respiratory failure secondary to COPD, but may be poorly tolerated. Preliminary evidence suggests nasal high-flow (NHF) therapy may improve hypercapnia in COPD and be well tolerated. We compared NHF and NIV in people with COPD and chronic hypercapnic respiratory failure. Methods: Single-blind randomized controlled two-way cross-over single-centre trial was conducted in New Zealand. Twenty-four participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 36 publications
1
28
0
3
Order By: Relevance
“…McKinstry et al . performed a randomized cross‐over trial to compare the efficacy of nasal high‐flow therapy against NIMV in stable hypercapnic COPD patients and showed that nasal high‐flow therapy was able to reduce patients' PaCO 2 ; however, overall, it was less effective than NIMV in reducing PCO 2 (by ~3 mm Hg) . As expected, nasal high‐flow therapy was much better tolerated than NIMV.…”
Section: Novel Approaches To Hypercapnic Respiratory Failurementioning
confidence: 78%
See 3 more Smart Citations
“…McKinstry et al . performed a randomized cross‐over trial to compare the efficacy of nasal high‐flow therapy against NIMV in stable hypercapnic COPD patients and showed that nasal high‐flow therapy was able to reduce patients' PaCO 2 ; however, overall, it was less effective than NIMV in reducing PCO 2 (by ~3 mm Hg) . As expected, nasal high‐flow therapy was much better tolerated than NIMV.…”
Section: Novel Approaches To Hypercapnic Respiratory Failurementioning
confidence: 78%
“…A more novel approach may be using nasal high‐flow therapy, which delivers humidified air (with or without supplemental oxygen) and is much better tolerated compared with NIMV . McKinstry et al .…”
Section: Novel Approaches To Hypercapnic Respiratory Failurementioning
confidence: 99%
See 2 more Smart Citations
“…McKinstry et al . have performed a randomized crossover study comparing NHF to NIV in stable hypercapnic subjects with obstructive lung disease and have also showed a measurable reduction in transcutaneous CO 2 of 2.5 mm Hg, which is, however, inferior to the 5.3 mm Hg reduction achieved with NIV . Another prior prospective study examined the effect of NHF on transcutaneous CO 2 in acutely exacerbating hypercapnic patients and similarly found a measurable but smaller reduction of 1.4 mm Hg .…”
mentioning
confidence: 98%